Prospects for Sugar palm (Arenga pinnata MERR) Development for Food and Energy Security - FS, Harahap; Hilwa, Walida; Rosmidah , Hasibuan; Abdul, Rauf; T., Sabrina; Benny, Hidayat; Rahmawaty, Rahmawaty; DE, Harahap; Parmanoan , Harahap (Journal of Saintech Transfer, 2020)
Abstract The purpose of this activity is to provide information about how the Prospect of Palm Plant Development (Arenga pinnata Merr) for food and energy security as well as processed products from palm trees, so that it is useful for the community, encouraging community awareness and awareness to preserve the environment. This activity was carried out in Buluh Awar Village, Sibolangit District, Deli Serdang Regency, involving the community in Buluh Awar Village and the Teaching Staff of the Agrotechnology Study Program, Faculty of Science and Technology, Biology Education Study Program, Teaching and Education Faculty, Labuhan Batu University, Postgraduate Study Program in Agrotechnology, Faculty Agriculture of the University of North Sumatra and the Faculty of Forestry of the University of North Sumatra. Agrotechnology Study Program, Faculty of Agriculture, Muhammadiyah University, South Tapanuli, Agrotechnology Study Program, Faculty of Agriculture, Graha Nusantara University, Padang Sidempuan. The main problem is the planting of sugar palm, which is generally not yet cultivated so that crop productivity is low and it is feared the plant population will decline. Since sugar palm plants have economic, social, cultural and conservation functions, it is wise to cultivate sugar palm and rehabilitate plants that grow naturally and irregularly in order to increase plant productivity. The results of the activity show that the cultivation of palm sugar plant has good hopes or prospects in the future. Processed products from palm plants such as sugar, drinks, and vinegar can be used to improve food security, while bioethanol can be used as an alternative energy source.